PERBEDAAN SUPLEMENTASI TABLET FE DAN TABLET FE PLUS VITAMIN C TERHADAP KENAIKAN KADAR HEMOGLOBIN PADA SISWI ANEMIA DI SMPNEGERI 4 MANDIRAJA KABUPATEN BANJARNEGARA - Sri Wahyuni; Astidio Noviardhi; Arintina Rahayuni (Poltekkes Kemenkes Semarang, 2017)
Background: Anemia is a nutritional problem in the world, especially in developing countries.Young women were among those prone to suffer from anemia because young women in its infancy and the monthly menstruation in Indonesia anemia prevalence of 57.1% in the suffering of young women (Dyah, 2011).The prevalence of anemia in Banjarnegara Regency in 2015 is 17, 6%.Objective:to know differences of tablets fe supplementation and tablets fe plus vitamin c on hemoglobin increase at anemia students in SMP Negeri 4 Mandiraja district Banjarnegara.Methods: This study was included in the nutrition research community.This type of research is quasi experiment (quasi experimental) approach pretest-posttest control group.Samples taken are anemic girls were 40 students and divided by 2 is purposiv e random sampling.The data collected is hemoglobin levels,feed intake and medication adherence.Test is a statistical test used paired t test with a confidence level of 95%.Results: The mean increase in hemoglobin of iron tablet supplementation group amounted to 0.611 g%, the average - average increase in hemoglobin to a batch of tablets suplemntasi Fe plus v itamin C of 0.475%Conclusion:There significant difference to the rise in hemoglobin of iron tablet supplementation group (p = 0.002), there was no significant difference to the rise in hemoglobin levels pad a tablet supplementation group Fe plusv itamin C (p = 0.079).There is no significant difference to the rise in hemoglobin levels before and after administration of suplementas i tablet tablet Fe and Fe plusv itamin C (p = 0.627).Suggested for schools should regularly carry out examination of hemoglobin, and the students should be able to set the pattern m will be nutritionally balanced.